Promoting Energy Access Projects under the Clean Development Mechanism : Standardized Baselines and Suppressed Demand - Gadde, Harikumar; Platonova-Oquab, Alexandrina; Affouda, Leon Biaou; Godin, Julie; Oppermann, Klaus (World Bank, Washington, DC, 2014)
New concepts under the Clean Development Mechanism (CDM), namely standardized baselines and suppressed demand, should facilitate the implementation of CDM energy access projects, particularly in Least Developed Countries (LDCs), by reducing transaction costs and reflecting the real emission reductions achieved. Governments and authorities in LDCs can play a prominent role in making these new CDM opportunities available. The improvement of the regulatory framework can facilitate the development of innovative carbon-based financing schemes required for successful scaling-up of CDM energy access projects in LDCs. The main purpose of this paper is to outline how the new CDM concepts of standardized baselines and suppressed demand may be used to promote energy access projects under the CDM, in the context of new and expanded role of host country Designated National Authorities (DNAs). In the process, the paper also identifies challenges in the use of these concepts and opportunities for further simplification. By way of illustration, one specific energy access technology, solar home systems, is analyzed in detail. The paper is organized as follows: chapter one is introduction; chapter two provides an overview of the current status of CDM projects in LDCs; chapter three introduces energy access projects in LDCs; chapter four outlines new approaches under the CDM for energy access projects; chapter five goes into the challenges for the application of standardized baselines in LDCs; and chapter six gives recommendations on implementing the new CDM concepts.